Reflexiones en torno a la línea editorial de la revista Enseñanza de las Ciencias - Sanmartí Puig, Neus; Azcárate, Carmen (Enseñanza de las Ciencias. Revista de investigación y experiencias didácticas, 1997)
The aim of this article is to inform about some thoughts and decisions taken by Ensefianza de las Ciencias journal editorial staff about the criteria for selecting articles. We believe that this criteria should be discussed in order to make possible an effective response to the needs of the teaching and research communities that constitute the public of the journal.